Role of filtration in managing the risk from Cryptosporidium in commercial swimming pools – a review - Wood, Martin; Simmonds, Lester; MacAdam, Jitka; Hassard, Francis; Jarvis, Peter; Chalmers, Rachel M. (IWA Publishing, 2019)
Most commercial swimming pools use pressurised filters, typically containing sand media, to remove suspended solids as part of the water treatment process designed to keep water attractive, clean and safe. The accidental release of faecal material by bathers presents a poorly quantified risk to the safety of swimmers using the pool. The water treatment process usually includes a combination of maintaining a residual concentration of an appropriate biocide in the pool together with filtration to physically remove particles, including microbial pathogens, from the water. However, there is uncertainty about the effectiveness of treatment processes in removing all pathogens, and there has been growing concern about the number of reported outbreaks of the gastrointestinal disease cryptosporidiosis, caused by the chlorine-resistant protozoan parasite Cryptosporidium. A number of interacting issues influence the effectiveness of filtration for the removal of Cryptosporidium oocysts from swimming pools. This review explains the mechanisms by which filters remove particles of different sizes (including oocyst-sized particles, typically 4–6 μm), factors that affect the efficiency of particle removal (such as filtration velocity), current recommended management practices, and identifies further work to support the development of a risk-based management approach for the management of waterborne disease outbreaks from swimming pools.
Keywords: Cryptosporidium oocysts; filtration; particle counting; swimming pools; turbidity